(untitled) (Journal of Comparative & International Higher Education, 2023)
This paper explores the relationship between embodiment and visual representations of racial diversity on university campuses. The study analyzes the visuals found on the websites of international student offices at all twelve Swiss universities. Using a discourse theoretical approach as a basis for qualitative document analysis, the paper identifies examples of racially embodied and disembodied presence and absence that govern context-specific forms of representation (Hook, 2008; Lentin, 2019). These findings suggest a novel interdisciplinary understanding of Whiteness in Switzerland that characterizes racialized space as not only characterized by the presence of White bodies but also their (partial) absence. Furthermore, this research brings the undertheorized aspect of race to the fore within studies of international higher education, particularly in the underrepresented topic of visual discourses in Europe. Finally, the paper discusses the need for nuanced understandings of diversity representation in education.